The effect of alendronate on resorption of the alveolar bone following tooth extraction - (:unkn) unknown (CHURCHILL LIVINGSTONE, 2004)
Maintenance of alveolar bone width and height following tooth loss is essential with regard to the restoration of missing teeth with endosseous dental implants or prosthodontics approaches. A various amount of alveolar ridge resorption is likely to occur after tooth extraction at the buccal and lingual alveolar bone plates. Bisphosphonates, alendronate, is well known for its potent inhibition of osteoclast-mediated bone resorption. The objective of this study was to examine the inhibitory effect of alendronate on alveolar bone resorption following tooth extraction in rats. Male Wistar Albino rats were divided into three groups: baseline group, saline-treated group and alendronate-treated group. The saline-treated group was administered with daily saline solution for 2 and 4 weeks respectively while the alendronate-treated group was given a daily amount of 0.25 mg/kg alendronate subcutaneously for the same periods. The level of urinary calcium, creatinine, and serum calcium, alkaline phosphatase and phosphate were measured. Serum alkaline phosphatase level was measured as a marker of osteoblastic activity. Histopathological sections of 4 mum thickness were obtained from the right first mandibular molar region in a bucco-lingual direction. The number of osteoclasts, osteoblasts, and haversian canals, the number and size of resorptive lacunae, and osteoid formation were evaluated histopathologically. The mean thickness of buccal and lingual alveolar bone was measured. In the alendronate-treated group, both buccal and lingual alveolar bone volume reduction was significantly less than the saline treated group. Significant reduction in serum and urinary calcium levels and the number of osteoclasts revealed the pronounced suppression of bone resorption in the alendronate-treated group.
Keywords: alendronate; bone resorption; extraction; rat; MUCOPERIOSTEAL FLAP SURGERY; VACUOLAR H+-ATPASE; BISPHOSPHONATE ALENDRONATE; POSTMENOPAUSAL WOMEN; PAGETS-DISEASE; LOCAL-DELIVERY; RISEDRONATE; ETIDRONATE; APOPTOSIS; TURNOVER